Crescimento demográfico e saneamento básico nas capitais regionais do Brasil - Tais Goncalves Neto de Oliveira (2017)
Brazil has experienced important changes in its rate of population and urban growth, which began near the end of the 1960s, resulting in the decline of natural growth, the redirection of migratory flows and the spatial redistribution of the population. The 1970s already showed signs of industrial decentralization in Brazil, which became clear from 1980 onwards. The restructuration of the urban network and the rise of new territorial management centers weakened rural-to-urban migratory flows that presented long distance and inter-regional migration, being replaced by urban-to-urban flows, predominantly of short distance and intra-regionals flows. Some urban centers, located in the countryside, developed economically and became established as regional centers, since they became areas of concentration for some economic activities that stirred up the economy of the region and its surroundings, as for example, the municipalities that, within the urban hierarchy, were classified as regional capitals by the Brazilian Institute of Geography and Statistics (IBGE). However, many municipalities seemed not to be prepared to absorb the impacts of population growth, especially in relation to the infrastructure of urban services, and that was aggravated in some cases by the inability of the government to intervene. This study aims to show the recent scenario (between the years of 1991 and 2010) and to present projections of the access to basic sanitation services in the Brazilian regional capitals for the years of 2018, 2023 and 2033, considering a scenario of where the growth trends of the number of permanent private households and the number permanent private households with access to access to water supply by general network, sewage by general network or septic tank and garbage collection are maintained through time. For that purpose, data from the demographic census of 1991, 2000 and 2010 were used, which allowed the proposition of a general index of municipal basic sanitation and allowed checking of the fulfillment of the basic sanitation goals established by the National Plan for Basic Sanitation (PLANSAB), published in 2013. Among the municipalities that presented the worst percentages of access to the variables related to basic sanitation, Marabá and Santarém stand out. Considering the projections, it should be noted that between the 64 regional capitals analyzed, 53 of them will probably not reach the goal for water supply in 2018, 54 in 2023, and 48 in 2033. In relation to the sewage sanitation, it is expected that 21 municipalities will not reach the goals established by the National Plan in 2018, 22 in 2023, and 27 in 2033. In relation to garbage collection, seven municipalities will not reach the goals in 2018, 2023 and 2033. Of all the regional capitals, Barbalha, Marabá, Vitória da Conquista, Petrolina e Juazeiro stand out, as they should not reach the limits established by any of the goals, in any area of sanitation, in any of the years. The results presented, although exploratory and specific to basic sanitation, can be useful as parameters to subsidize the formulation of public policies at various government levels, including the municipal level, indicating the cases in which there is greater need to intensify investments.